2021
DOI: 10.3390/polym13091467
|View full text |Cite
|
Sign up to set email alerts
|

Application of Polymer Drugs with Cerium Dioxide Nanomolecules and Mesenchymal Stem Cells for the Treatment of Skin Wounds in Aged Rats

Abstract: The urgency of the problem of wound healing is not in doubt, given the global trend of an increase in the number of operations and injuries with skin damage, as well as the lack of universal means of treating wounds. Study Objective: To compare the effectiveness of the developed drugs, smart polymeric nano-drug with cerium oxide nanoparticles (SPN), and smart polymeric nano-drug in combination with mesenchymal stem cells (SPN + SC) on the healing process of skin wounds. Material and methods. An experimental st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The composition and technology of the drugs PCCD, MSC, and PCCD + MSC have been published previously [30][31][32][33][34].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The composition and technology of the drugs PCCD, MSC, and PCCD + MSC have been published previously [30][31][32][33][34].…”
Section: Methodsmentioning
confidence: 99%
“…However, not enough research has yet been done investigating this new direction to provide data that meet all the requirements of evidence-based medicine. In our previous research, we developed new dressing biomaterials for the treatment of wounds containing polymers, mesenchymal stem cells, and nanoparticles of cerium dioxide (CeO2), and demonstrated their preliminary safety and efficacy [30][31][32][33][34]. We have chosen CeO2 nanoparticles as the metal included in our biomaterials because previous studies have shown that it has low toxicity and high biocompatibility, as well as the ability, depending on the changing pH of the wound, to provide electron transfer through the transition from Ce3+ to Ce4+ valence and vice versa [35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…CeO 2 ‐based materials with different structures have been put forward and made good application progress such as nanocubes, [ 12 ] electrospun membranes, [ 13 ] hollow spheres, [ 14 ] hydrogels, [ 15 ] and scaffolds. [ 2d,10,16,17 ] In 2018, Huang et al prepared chitosan‐coated CeO 2 nanocubes (CCNs) and studied the potential application of CCNs in the field of cutaneous wound healing. [ 12 ] The results of the study confirm that CCNs are more effective than clinically used recombinant human epidermal growth factors in promoting wound healing.…”
Section: Application For Wound Healingmentioning
confidence: 99%
“…In 2021, Russian researchers used a polymeric nanocomposite made of nano-cerium dioxide and mesenchymal stem cells (MSC) to heal wounds. The use of smart scaffolding results in anti-inflammation, cell proliferation, and re-epithelialization ( Silina et al., 2021 ). Janani et al.…”
Section: Skin Tissue Engineeringmentioning
confidence: 99%